PROPAGANDA POLITIK DALAM ISI KANDUNGAN HADIS-HADIS PALSU - Alkadri Alkadri (Borneo : Journal of Islamic Studies, 2021)
The status of false hadith in the science of hadith cannot be used as an hujjah. But, its content can reflect the socio-political dynamics of his time. Especially related to leadership, group interests and theology. For that, it is necessary to study in detail the theme of political propaganda in the content of false hadiths. The focus of the study: (1) how the content of the hadith, (2) what is the motive behind its spread, (3) what is the wisdom. Methods of discussion, literature study through a hermeneutic approach. Data analysis using content analysis. Sources of data on the books of al-Maudhu’at and al-fawa`id. Findings of the discussion: (1) the content of the hadith in the form of black propaganda in the form of false news, hatred, worship, testimony, leading to certain opinions in the name of the prophet and god , (2) the motive for creating an individual cult on the figure of the khalifah and group fanatics, (3) the wisdom of today is that black propaganda labeled islam can tarnish the teachings of islam itself as a blessing for all the worlds. This condition can be associated with the ebb and flow of the relationship between shiite imams and islamic radical-arabism in the form of claims of truth, entering heaven for those who agree. On the other hand, misguided claims, go to hell for those who do not agree in matters of worship or theology so as to give rise to group fanatics. The novelty of the discussion in the form of offering the concept of understanding false hadiths through a hermeneutic approach.